Plasmodium falciparum: a method for the amplification of S antigens and its application to laboratory and field samples. - Kyes, S; Craig, A; Marsh, K; Newbold, C (1993)
Polymerase chain reaction amplification of several polymorphic genes has been used to study the population biology of Plasmodium falciparum. S antigen is particularly suitable for such studies, but difficulties in the amplification of this gene have precluded its use. Here we describe a simple method for the amplification of S antigen and show why previous attempts may have been unsuccessful. Data are presented from both laboratory and field isolates.